Contactless CAN interface for rail topologies - Wesemann, Derk; Wiite, Stefan; Bleikirch, Helmut (13th international CAN Conference - ICC)
Contactless interfaces are essential to different applications which rely on physical robustness and / or high modularity and movability. This work presents a solution for direct conversion of CAN signals for contactless capacitive coupling over an air gap. The coupling distances are short (in the range of less than 1 mm), but can be extended by a supporting rail which contains coupling electrodes and conductors to deliver the signals also over larger distances. A modulation scheme is implemented to maintain the functionality of dominant and recessive bit status. No additional controller is needed; the transceiver module replaces the CAN transceiver typically added to any microcontroller.